Assessment of Avoidable Losses Caused by Leaf Webber and Capsule Borer (Antigastra Catalaunalis Dup.) in Promising Sesame Varieties - Sundria, Man Mohan; Pandey, Shalini; Geat, Neelam; Kumhar, S. R. (Annals of Arid Zone, 2022)
An experiment was conducted during the kharif seasons of 2018 and 2019 with varieties viz., RT 346, RT 351, TKG 306, TKG 308, Rama, VRI 1, GT 10 and TKG 22 of sesame (Sesamum indicum L.) to assess the avoidable loss in seed yield due to leaf webber and capsule borer under rainfed conditions at ARS, Mandor. The performance of all the promising sesame varieties grown under protected conditions were found significantly superior over the unprotected conditions, except in case of two varieties viz., TKG-308 and VRI-1 at capsule stage only. The varieties viz., RT 351, TKG 308 and GT 10 were found significantly superior over all other varieties of sesame grown under both the protected and unprotected conditions. Avoidable loss recorded ranged from 25.51 to 61.45% in different varieties under protected condition in comparison to unprotected conditions, maximum in RT 351 and minimum in VRI 1 due to leaf webber and capsule borer. The pest caused significant loss in seed yield under unprotected condition in comparison to protected condition. The varieties viz., TKG 308, RT 351 and GT 10 performed good under unprotected conditions and gave highest seed yield, the variety GT 10 stands first in respect to record lowest damage (9.58%, 15.89% and 5.40% at vegetative, flowering and capsule stage, respectively) under unprotected conditions. Varieties viz., RT 351, TKG 308 and GT 10 gave highest seed yields of 444 kg ha-1, 433 kg ha-1 and 397 kg ha-1, respectively, under protected condition. Overall, all the varieties performed well in protected conditions and their yield potential were also increased.